Spin states of quasi-two-dimensional electrons - Eremko, A.A. (Reports of the National Academy of Sciences of Ukraine, 2015)
Using the example of quasi-two-dimensional electrons, it is shown that the full description of the electron spin degree of freedom requires one to consider relativistic conservation laws, which are fulfilled only approximately in a non-relativistic theory.